Infidels and empires in a new world order: early modern Spanish contributions to international legal thought - Lantigua, David M. (Law and Christianity, 2020)
Before international relations in the West, there were Christian-infidel relations. Infidels and Empires in a New World Order decenters the dominant story of international relations beginning with Westphalia in 1648 by looking a century earlier to the Spanish imperial debate at Valladolid addressing the conversion of native peoples of the Americas. In addition to telling this crucial yet overlooked story from the colonial margins of Western Europe, this book examines the Anglo-Iberian Atlantic to consider how the ambivalent status of the infidel other under natural law and the law of nations culminating at Valladolid shaped subsequent international relations in explicit but mostly obscure ways. From Hernán Cortés to Samuel Purchas, and Bartolomé de las Casas to New England Puritans, a host of unconventional colonial figures enter into conversation with Francisco de Vitoria, Hugo Grotius, and John Locke to reveal astonishing religious continuities and dissonances in early modern international legal thought with important implications for contemporary global society.